A Review of the Mechanism of Vascular Endothelial Injury in Immunoglobulin A Vasculitis - Xu, Shanshan; Han, Shanshan; Dai, Yanlin; Wang, Long; Zhang, Xia; Ding, Ying (Frontiers in Physiology, 2022)
Henoch-Schönlein purpura, also known as Immunoglobulin A vasculitis (IgAV), is the most common form of childhood vasculitis It is characterized by cutaneous hemorrhage, resulting from red blood cell leakage into skin or mucosae, possibly caused by damage to small blood vessels. These acute symptoms usually disappear without treatment. Endothelial cells are distributed on the inner surfaces of blood vessels and lymphatic vessels, which are not only important metabolic and endocrine organs in the body but are also the primary targets of external stimuli and endogenous immune activity. Injury to endothelial cells is a feature of Henoch-Schönlein purpura. Endothelial cell damage may be related to the deposition of immune complexes, activation of complement, inflammatory factors and chemokines, oxidative stress, hemodynamics, and coagulation factors. Both epigenetics and genetic diversity provide a genetic background for endothelial cell injury. Here, research on the role of endothelial cells in allergic purpura injury is reviewed.